2017
DOI: 10.1111/ctr.13011
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity is associated with ABO‐nonidentical liver transplantation in the United States

Abstract: United Network for Organ Sharing (UNOS) policies allow for ABO-nonidentical liver transplantation (LT) in candidates with Model for End-Stage Liver Disease (MELD) scores greater than 30. Previous studies showed ABO-nonidentical LT resulted in an 18% and 55% net gain in livers for B and AB candidates. These results suggested that the current liver ABO allocation policies may need refinement. There are, however, strong associations between ABO blood groups and race/ethnicity. We hypothesized that race/ethnicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…We recently conducted an analysis of ABO nonidentical liver transplantation using a more contemporary cohort of liver transplant recipients in the United States using data from the UNOS registry from 2013 to 2015. In this cohort, the vast majority (137/154 [87%]) of non‐status 1 ABO‐incompatible transplants were A2→O . Additional analyses of posttransplant survival rates demonstrated that the recipients of A2→O grafts had similar 1‐year survival rates (hazard ratio 1.11, 95% confidence interval 0.64‐1.92, P = 0.72) compared with recipients of O→O grafts in adjusted multivariable Cox models (Fig.…”
Section: Clinical Outcomesmentioning
confidence: 81%
See 3 more Smart Citations
“…We recently conducted an analysis of ABO nonidentical liver transplantation using a more contemporary cohort of liver transplant recipients in the United States using data from the UNOS registry from 2013 to 2015. In this cohort, the vast majority (137/154 [87%]) of non‐status 1 ABO‐incompatible transplants were A2→O . Additional analyses of posttransplant survival rates demonstrated that the recipients of A2→O grafts had similar 1‐year survival rates (hazard ratio 1.11, 95% confidence interval 0.64‐1.92, P = 0.72) compared with recipients of O→O grafts in adjusted multivariable Cox models (Fig.…”
Section: Clinical Outcomesmentioning
confidence: 81%
“…3). 8 This demonstrated that MELD score or relative donor scarcity is not the sole driver of A2!O transplantation, and that these differences may reflect center-level variations or protocols, which warrants further investigation.…”
Section: Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…This delineation was used as UNOS allocation rules governing donors diverge at age 18 . Donor and waitlist candidate UNOS regions were categorized based on the median allocation MELD score at transplantation during the study period: “low” for regions with MELD <27, “medium” for regions with MELD ≥27 and <30, and “high” for regions with MELD ≥30 similar to the categorization used in a previous analysis …”
Section: Methodsmentioning
confidence: 99%